2009
DOI: 10.1080/08858190802664834
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics, Health Beliefs, and the Accuracy of Cancer Knowledge

Abstract: Background Recent studies have found that knowledge about cancer prevention and treatment differs across ethnic and socioeconomic status (SES) backgrounds, which could directly impact our decisions to engage in protective health behaviors. In this study, we examined sociodemographic-based differences in cancer knowledge and health beliefs and examined differences in the accuracy of the cancer knowledge based on health beliefs. Methods Cross-sectional surveys were conducted between July 1995 and March 2004 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 25 publications
5
40
0
Order By: Relevance
“…Rutten and colleagues found that respondents with lower levels of income and education lacked adequate knowledge and appropriate beliefs about smoking and cancer (20). Consistent with another study, knowledge about smoking increased with higher educational achievement and annual household income (39).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Rutten and colleagues found that respondents with lower levels of income and education lacked adequate knowledge and appropriate beliefs about smoking and cancer (20). Consistent with another study, knowledge about smoking increased with higher educational achievement and annual household income (39).…”
Section: Discussionsupporting
confidence: 64%
“…Low socioeconomic status was associated with lower knowledge scores (38)(39)(40)(41). Rutten and colleagues found that respondents with lower levels of income and education lacked adequate knowledge and appropriate beliefs about smoking and cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…8,9,[11][12][13][14][15][16][17][18][19] Similar findings have emerged from international research conducted in Australia and Sweden. 13,20 Complicating our understanding of SES and melanoma epidemiology is the complex relationship among socioeconomic factors, environmental risk factors, sun-exposure behavior, 21 awareness of melanoma prevention, access to primary care and melanoma screening, [22][23][24] and potential variation in ultraviolet (UV) exposure related to differences in outdoor recreation and leisure, 25 a product of SES itself. Intensive research efforts focusing on all aspects of melanoma are vital to reducing the incidence and mortality associated with the disease.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…American men are less likely than women to have knowledge of and adopt cancer preventive health behaviors, including reducing dietary fat intake and maintaining healthy body weights (Wilkinson, Vasudevan, Honn, Spitz, & Chamberlain, 2009). Overall, American and British men are more likely to suffer from and die of most types of cancer than are women (Cancer Research UK, 2009;Jemal et al, 2009).…”
Section: Men Masculinities and Prostate Cancermentioning
confidence: 99%